Legal and Financial Literacy Programs for Sustainable Social Development - Abdal Ahmed; Ahmad Reza Hariyadi; Rusdiana Priatna Wijaya (Pusat Riset dan Inovasi Nasional Mabadi Iqtishad Al Islami, 2026)
This community engagement program aimed to strengthen community empowerment through legal and financial literacy initiatives designed to support sustainable social development in Uttarakhand, India. The program involved rural and semi-urban communities, including local residents, youth groups, small entrepreneurs, and women’s associations, many of whom demonstrated limited understanding of legal rights, financial management, and sustainable economic practices. These limitations reduced their participation in local development initiatives and community decision-making processes. To address these challenges, the program implemented participatory workshops, legal awareness campaigns, financial literacy training, and mentoring activities over a three-month period involving 60 participants. The findings indicated significant improvements in participants’ understanding of legal rights, budgeting practices, savings management, entrepreneurial planning, and financial decision-making skills. Qualitative results further revealed stronger community participation, increased confidence in social engagement, and improved awareness regarding social responsibility and sustainable development. Participants also became more actively involved in local economic and community activities after completing the program.